Zuhause fremd Russlanddeutsche zwischen Russland und Deutschland - Ipsen-Peitzmeier, Sabine; Kaiser, Markus (bibliotheca eurasica, 2006)
Since the beginning of the 1990s, when the arrival of late repatriates from the former USSR reached its peak, Germany's scientific interest in the German-Russian, its history, its migration and its situation in German society is growing. Also the contributions of this volume are dedicated to these topics. However, what distinguishes them beyond their current reference is the German-Russian composition of the authors, who acquire the subject from their own perspective and thereby draw a complex picture.